Constraints on the Equations of State of stiff anisotropic minerals: rutile, and the implications for rutile elastic barometry. (22nd April 2019) - Zaffiro, Gabriele; Angel, Ross J.; Alvaro, Matteo
Abstract: We present an assessment of the thermo-elastic behaviour of rutile based on X-ray diffraction data and direct elastic measurements available in the literature. The data confirms that the quasi-harmonic approximation is not valid for rutile because rutile exhibits substantial anisotropic thermal pressure, meaning that the unit-cell parameters change significantly along isochors. Simultaneous fitting of both the diffraction and elasticity data yields parameters of K TR 0 = 205.14(15) GPa, K SR 0 = 207.30(14) GPa, K_TR0^′ = 6.9(4) in a 3rd-order Birch-Murnaghan Equation of State for compression, α V 0 = 2.526(16) × 10 – 5 K – 1, Einstein temperature θ E = 328(12) K, Anderson-Grüneisen parameter δ T = 7.6(6), with a fixed thermal Grüneisen parameter γ = 1.4 to describe the thermal expansion and variation of bulk modulus with temperature at room pressure. This Equation of State fits all of the available data up to 7.3 GPa at room temperature, and up to 1100 K at room pressure within its uncertainties. We also present a series of formulations and a simple protocol to obtain thermodynamically consistent Equations of State for the volume and the unit-cell parameters for stiff materials, such as rutile. In combination with published data for garnets, the Equation of State for rutile indicates that rutile inclusions trapped inside garnets in metamorphic rocks should exhibit negative residual pressures when measured at room conditions.